1988
DOI: 10.1002/jcp.1041350110
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of granulocytes and mast cells in cultures of mouse bone marrow stimulated with interleukin‐3

Abstract: Bone marrow cells in liquid culture with interleukin 3 produce a population of non-adherent granulocytes and mast cells. Flow cytometry was used to identify granulocytes and mast cells on the basis of the physical properties of perpendicular light scatter (PLS) and coulter volume (CV) as well as the expression IgE and CR3 receptors. Multicolor analysis indicated there were subpopulations of Thy1.2 positive cells which transiently appeared in these cultures and also expressed IgE receptors, CR3 receptors or nei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1992
1992
2002
2002

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…BMMC were generated essentially as described by Bender et al [37]. In short, unfractionated bone marrow cells from B6 or BALB.B mice were cultured at 2.5 × 10 5 cells/ml in supplemented RPMI 1640 medium containing 25 U/ml IL-3 (Pharmingen).…”
Section: Isolation Of Bone Marrow-derived and Peritoneal Mast Cellsmentioning
confidence: 99%
“…BMMC were generated essentially as described by Bender et al [37]. In short, unfractionated bone marrow cells from B6 or BALB.B mice were cultured at 2.5 × 10 5 cells/ml in supplemented RPMI 1640 medium containing 25 U/ml IL-3 (Pharmingen).…”
Section: Isolation Of Bone Marrow-derived and Peritoneal Mast Cellsmentioning
confidence: 99%
“…In part, our results suggest a close association between rat marrow cells resembling members of the mast cell lineage and early hemopoietic stemiprogenitor cells by expressing functional c-kit receptors and having high levels of Thy 1.1 on their surface. Other studies have shown that cells capable of developing into marrow-derived mast cells by IL-3 stimulation have been isolated from mouse marrow in a Thy 1.2' subset (Bender et al, 1988) and in a subset of CD-34+ human marrow cell progenitors (Kirshenbaum et al, 1991). Moreover, others show that human stem cell factor synergizes with IL-3 to stimulate mast lineage cells from this CD34 ' marrow subset (Kirshenbaum et al, 1992).…”
Section: Discussionmentioning
confidence: 99%
“…It is capable of producing nearly pure colonies of immature Ma cells similar to MMC after 2-4 weeks in culture with IL-3 as the principal stimulant. The population of Ma-CFC appears to be Thyl-positive and to express a high-affinity IgE receptor (Bender, van Epps & Stewart 1988, Rottem et al 1992. Ma-CFC is producing moremature cells of higher density (over 1.12 g/cm3), which are IL-3-independent, morphologically similar to differentiated Ma, and form small and medium colonies in vitro (Kanaruka et al 1988).…”
Section: Kinetics O F Eosinophils Basophils a N D Mast Cellsmentioning
confidence: 99%